Addiction to social networks considering sample of employees of several organizations of southeastern, Puerto Rico - Rosario Nieves, Ilia C. (2018)
The main objective of the research was to auscultate if the employees of companies use social network, if they have an addiction to technology, and how they use the internet during their working hours using a quantitative methodology with a Cross-sectional and descriptive approach. In order to measure the addiction to social networks, the instrument used was the Social Network Addiction Questionnaire (ARS) designed by Miguel Escurra Mayaute and Edwin Salas Blas (2014). 100 questionnaires were administrated. Of the socio-demographic data collected, the following stood out: 54% correspond to the public organization, 63% of the participants were female, and 96% of the participants use their cell phone to connect to social networks, while 70% do so through the computer. In a similar way, participants indicated to connect to social networks at their homes and at work. Regarding which social network Facebook is the most used, obtained the most percentage with 40%. The results revealed that there are statically significant differences by gender (F=5.34, p=.023), by amount of time they are connected (F=4.80, p=.002) and addiction to social networks.